The Impact of Gadget Use on Early Childhood Religious Value Development - Nurhayati Nurhayati; Nurul Hikma; Sita Awalunisah (STAI Hubbulwathan Duri, 2024)
Globalization has diverse interpretations depending on various fields of expertise, but generally implies a borderless world where interactions can occur freely. Official NET News highlights the influence of gadgets on children, particularly in relation to gaming habits and parental management of potential addictions. This study aims to explore the impact of gadget use on the religious development of children aged 4-6 at TK Negeri Pembina Samporoa Vatutela Tondo. A mixed-method approach, incorporating both quantitative and qualitative methods, was used over a three-week period. Observations covered various religious aspects including knowledge of Prophets and Messengers, Hajj rituals, and prayer movements. The findings indicate that gadget use can positively influence the development of religious values in children aged 4-6. The aspects of naming Prophets and Messengers, understanding Hajj rituals, and performing prayer movements show development as expected. In Group B1, gadget usage also varies, with some children engaging in online/offline games, watching YouTube, or using TikTok. Gadget use can be multifaceted, serving as a means for both entertainment and educational development, particularly in the religious sphere. The balance between these uses and potential influences on children's development warrants further investigation.